Strategi Pelayanan CRM Dalam Meningkatkan Brand Loyalty Zipzap Corporation - Linda Hanifah Septiana Putri; Andri Prasetyo Yuwono (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Customer Relationship Management (CRM) is one of the business strategies that companies can employ to foster positive relationships between the company and its customers. This research aims to explore and analyze the CRM service strategies employed by Zipzap Corporation, examining the factors influencing the effectiveness of these strategies in enhancing brand loyalty for Zipzap Corporation. The research methodology utilized is qualitative, involving interviews with both Zipzap Corporation customers and customer service employees. The findings reveal that Zipzap Corporation implements CRM strategies encompassing post-sales and delivery service stages. Customer perspectives indicate that factors such as communication ease, product quality, and trust are primary considerations when selecting a vendor. These factors are integral to the CRM service strategy, aiming to enhance brand loyalty for Zipzap Corporation. This study provides insights into CRM service strategies that companies can adopt to build strong customer relationships, ultimately contributing to the overall business objectives and sustainability.